Hollow fiber nanofiltration membranes for surface water treatment: Performance evaluation at the pilot scale. (August 2021) - Sengur-Tasdemir, Reyhan; Urper-Bayram, Gulsum Melike; Turken, Turker; Ates-Genceli, Esra; Tarabara, Volodymyr V.; Koyuncu, Ismail
Abstract: Four types of hollow fiber nanofiltration membranes were fabricated and tested during pilot scale treatment of surface water taken from Istanbul Ömerli Lake Reservoir. Membrane types included: polymer thin film composite, reinforced thin film composite, TiO2 -polymer thin film nanocomposite, and Aquaporin-polymer reinforced thin film composite. Interfacial polymerization procedure was used to form the polyamide separation layer for all membrane types. The amount of permeate water collected from membranes was controlled by membrane fouling. In terms of productivity, the membranes were ranked as follows: reinforced Aquaporin membrane (6.30 L/m 2 /h) > TiO2 incorporated membrane (5.69 L/m 2 /h) > reinforced thin film composite membrane (4.76 L/m 2 /h) > polymeric thin film composite membrane (3.24 L/m 2 /h). TiO2 -incorporated membranes had the highest initial flux while reinforced thin film composite membranes had the highest removals for each water constituents tested (MgCl2, tannic acid, synthetic lake water, pre-filtered lake water). The study points to the practicability and promise of hollow fiber nanofiltration membranes for surface water treatment applications.